Stay or go? Neuronal activity in medial frontal cortex during a voluntary tactile preference task in head-fixed mice. (June 2021) - Keyes, Alex L.; Kim, Young-cho; Bosch, Peter J.; Usachev, Yuriy M.; Aldridge, Georgina M.
Graphical abstract: Highlights: We developed a tactile stimulus task utilizing preference, not reflexive responses. The tactile stimulus task has broad applicability for behavior and in vivo imaging. A subset of medial M2 neurons are modulated by changes in sensory stimuli. Abstract: The decision to move is influenced by sensory, attentional, and motivational cues. One such cue is the quality of the tactile input, with noxious or unpleasant sensations causing an animal to move away from the cue. Processing of painful and unpleasant sensation in the cortex involves multiple brain regions, although the specific role of the brain areas involved in voluntary, rather than reflexive movement away from unpleasant stimuli is not well understood. Here, we focused on the medial subdivision of secondary motor cortex, which is proposed to link sensory and contextual cues to motor action, and tested its role in controlling voluntary movement in the context of an aversive tactile cue. We designed a novel, 3D-printed tactile platform consisting of innocuous (grid) and mildly noxious (spiked) surfaces (50:50 % of total area), which enabled monitoring neuronal activity in the medial frontal cortex by two-photon imaging during a sensory preference task in head-fixed mice. We found that freely moving mice spent significantly less time on a spiked-surface, and that this preference was eliminated by administration of a local anesthetic. At the neuronal level, individual neurons were differentially modulated specific to the tactile surface encountered. At the population level, the neuronal activity was analyzed in relation to the events where mice chose to "stop-on" or "go-from" a specific tactile surface and when they "switched" surfaces without stopping. Notably, each of these three scenarios showed population activity that differed significantly between the grid and spiked tactile surfaces. Collectively, these data provide evidence that tactile quality is encoded within medial frontal cortex. The task pioneered in this study provides a valuable tool to better evaluate mouse models of nociception and pain, using a voluntary task that allows simultaneous recording of preference and choice.